Insect growth regulators as potential insecticides to control olive fruit fly (Bactrocera oleae Rossi): insect toxicity bioassays and molecular docking approach. Issue 1 (22nd June 2012) - Bengochea, Paloma; Christiaens, Olivier; Amor, Fermín; Viñuela, Elisa; Rougé, Pierre; Medina, Pilar; Smagghe, Guy
Abstract BACKGROUND: Olive fruit fly, Bactrocera oleae (Rossi), is a key pest in olive orchards, causing serious economic damage. To date, the pest has already developed resistance to the insecticides commonly applied to control it. Thus, in searching for new products for an accurate resistance management programme, targeting the ecdysone receptor (EcR) might provide alternative compounds for use in such programmes. RESULTS: Residual contact and oral exposure in the laboratory of B. oleae adults to the dibenzoylhydrazine‐based compounds methoxyfenozide, tebufenozide and RH‐5849 showed different results. Methoxyfenozide and tebufenozide did not provoke any negative effects on the adults, but RH‐5849 killed 98‐100% of the treated insects 15 days after treatment. The ligand‐binding domain (LBD) of the EcR of B. oleae (BoEcR‐LBD) was sequenced, and a homology protein model was constructed. Owing to a restricted extent of the ligand‐binding cavity of the BoEcR‐LBD, docking experiments with the three tested insecticides showed a severe steric clash in the case of methoxyfenozide and tebufenozide, while this was not the case with RH‐5849. CONCLUSION: IGR molecules similar to the RH‐5849 molecule, and different from methoxyfenozide and tebufenozide, might have potential in controlling this pest. Copyright © 2012 Society of Chemical Industry